Azilsartan Suppresses Osteoclastogenesis and Ameliorates Ovariectomy-Induced Osteoporosis by Inhibiting Reactive Oxygen Species Production and Activating Nrf2 Signaling - Pan, Bin; Zheng, Lin; Fang, Jiawei; Lin, Ye; Lai, Hehuan; Gao, Jiawei; Pan, Wenzheng; Zhang, Yejin; Ni, Kainan; Lou, Chao; He, Dengwei (Frontiers in Pharmacology, 2021)
Osteoporosis is characterized by a decrease in bone mass and destruction of the bone microarchitecture, and it commonly occurs in postmenopausal women and the elderly. Overactivation of osteoclasts caused by the inflammatory response or oxidative stress leads to osteoporosis. An increasing number of studies have suggested that intracellular reactive oxygen species (ROS) are strongly associated with osteoclastogenesis. As a novel angiotensin (Ang) II receptor blocker (ARB), azilsartan was reported to be associated with the inhibition of intracellular oxidative stress processes. However, the relationship between azilsartan and osteoclastogenesis is still unknown. In this study, we explored the effect of azilsartan on ovariectomy-induced osteoporosis in mice. Azilsartan significantly inhibited the receptor activator of nuclear factor-κB ligand (RANKL)-mediated osteoclastogenesis and downregulated the expression of osteoclast-associated markers (Nfatc1, c-Fos, and Ctsk) in vitro. Furthermore, azilsartan reduced RANKL-induced ROS production by increasing the expression of nuclear factor erythroid 2-related factor 2 (Nrf2). Mechanistically, azilsartan inhibited the activation of MAPK/NF-κB signaling pathways, while Nrf2 silencing reversed the inhibitory effect of azilsartan on MAPK/NF-κB signaling pathways. Consistent with the in vitro data, azilsartan administration ameliorated ovariectomy (OVX)-induced osteoporosis and decreased ROS levels in vivo. In conclusion, azilsartan inhibited oxidative stress and may be a novel treatment strategy for osteoporosis caused by osteoclast overactivation.